Vortex fluidic mediated transformation of graphite into highly conducting graphene scrolls. Issue 7 (19th June 2019) - Vimalanathan, Kasturi; Suarez-Martinez, Irene; Peiris, M. Chandramalika R.; Antonio, Joshua; de Tomas, Carla; Zou, Yichao; Zou, Jin; Duan, Xiaofei; Lamb, Robert N.; Harvey, David P.; Alharbi, Thaar M. D.; Gibson, Christopher T.; et al.
Abstract : A facile one step process has been developed to fabricate high yield graphene scrolls directly from graphite flakes using a sustainable metrics, with the 3D nanomaterial having remarkable properties, unraveling into buckled graphene sheets >450 °C and forming highly conducting electrical contacts. Abstract : Two-dimensional graphene has remarkable properties that are revolutionary in many applications. Scrolling monolayer graphene with precise tunability would create further potential for niche applications but this has proved challenging. We have now established the ability to fabricate monolayer graphene scrolls in high yield directly from graphite flakes under non-equilibrium conditions at room temperature in dynamic thin films of liquid. Using conductive atomic force microscopy we demonstrate that the graphene scrolls form highly conducting electrical contacts to highly oriented pyrolytic graphite (HOPG). These highly conducting graphite–graphene contacts are attractive for the fabrication of interconnects in microcircuits and align with the increasing interest in building all sp 2 -carbon circuits. Above a temperature of 450 °C the scrolls unravel into buckled graphene sheets, and this process is understood on a theoretical basis. These findings augur well for new applications, in particular for incorporating the scrolls into miniaturized electronic devices.